KORELASI FENOMENA MUKBANG ‎DENGAN MAKAN BERLEBIH-LEBIHAN ‎MENURUT QURAISH SHIHAB - Panjaitan, Hana Pertiwi (UIN Sumatera Utara Medan, 2024)
The Quran is the final holy book revealed to Prophet Muhammad, and no heavenly book will be revealed after the Quran. Islam teaches not to forbid good foods that have been made lawful by Allah as sustenance, with the condition of not overindulging in consuming these foods. Eating and drinking etiquette refers to the practices followed before, during, and after eating and drinking, in accordance with the teachings of the Prophet Muhammad (PBUH). However, in modern times, the term 'mukbang' has become popular, referring to videos or live broadcasts where a person intentionally eats large portions of food in front of the camera for the purpose of entertainment or as a spectacle. Given the various opinions that have been outlined, the author is interested in studying the mukbang phenomenon from the perspective of the Quran. This research is important to educate the Muslim community, particularly on the proper eating and drinking etiquette according to the Quran.Keywords: Mukbang, excessiveness, Quraish Shihab.